Effect of CTCF and Cohesin on the dynamics of RNA polymerase II transcription and coupled pre-messenger RNA processing - Liska, O (2013)
The CCCTC-binding factor (CTCF) is a versatile, multifunctional zinc-finger protein involved in a broad spectrum of cellular functions. In mammalian cells, CTCF functions together with the Cohesin complex, an essential regulator of sister chromatid cohesion. Together, CTCF and Cohesin have been shown to regulate gene expression at a genome-wide level in mammalian cells. In the yeast Saccharomyces pombe, Cohesin has been implicated in transcription termination of convergently transcribed genes, in a cell cycle dependent manner. The aim of this thesis was to investigate the possibility of direct transcriptional involvement of CTCF and Cohesin in human cells. The first model system applied for this experimental purpose was the β-globin gene with introduced canonical CTCF-binding sites replacing the endogenous Co- Transcriptional Cleavage (CoTC) element downstream of β-globin. The results obtained indicate that recruitment of CTCF to the β-globin 3` flanking region does not prevent read-through transcription. However, CTCF-binding does mediate RNA Polymerase II (Pol II) pausing at the site of recruited CTCF. This results in more efficient pre-mRNA 3` end processing and therefore rescues β-globin mRNA to wild type levels. Cohesin was not detected at the introduced CTCF-binding sites. These results are a contribution to our understanding of the spatio-temporal requirements for cotranscriptional events like 3` end pre-mRNA processing and Pol II kinetics. The second part of my thesis presents an investigation on the involvement of CTCF and Cohesin in lipopolysaccharide (LPS)-induced Tumor Necrosis Factor α (TNFα) gene expression regulation in human monocytes and differentiated M1- and M2-type macrophages. These studies provide first evidence of Cohesin recruitment to the TNFα gene body and its regulatory NFκB-binding sites. Differences in the recruitment profiles obtained indicate potential regulatory differences of TNFα among the three cell types. Preliminary data provide an insight into the effects on TNFα mRNA levels upon down-regulation of Cohesin subunits.